2014
DOI: 10.1021/ja507168t
|View full text |Cite
|
Sign up to set email alerts
|

A Potent α/β-Peptide Analogue of GLP-1 with Prolonged Action in Vivo

Abstract: Glucagon-like peptide-1 (GLP-1) is a natural agonist for GLP-1R, a G protein-coupled receptor (GPCR) on the surface of pancreatic β cells. GLP-1R agoinsts are attractive for treatment of type 2 diabetes, but GLP-1 itself is rapidly degraded by peptidases in vivo. We describe a design strategy for retaining GLP-1-like activity while engendering prolonged activity in vivo, based on strategic replacement of native α residues with conformationally constrained β-amino acid residues. This backbone-modification appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 45 publications
(53 reference statements)
2
106
0
Order By: Relevance
“…Indeed, α/β-VEGF-1 showed substantially greater resistance to proteinase K than the 59-mer α-peptide Z-VEGF. These observations are consistent with previous findings, involving other α-vs. α/β-peptide comparisons, that have shown that α→β replacements at multiple sites can substantially enhance polypeptide resistance to protease action (6)(7)(8)(9)35). Introduction of one additional Aib residue, to convert α/β-VEGF-1 into α/β-VEGF-2, conferred additional resistance to proteinase K (half-life, 670 min; >400-fold increase relative to Z-VEGF and >3,300-fold increase relative to α-VEGF-2).…”
Section: S-s S-s S-smentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, α/β-VEGF-1 showed substantially greater resistance to proteinase K than the 59-mer α-peptide Z-VEGF. These observations are consistent with previous findings, involving other α-vs. α/β-peptide comparisons, that have shown that α→β replacements at multiple sites can substantially enhance polypeptide resistance to protease action (6)(7)(8)(9)35). Introduction of one additional Aib residue, to convert α/β-VEGF-1 into α/β-VEGF-2, conferred additional resistance to proteinase K (half-life, 670 min; >400-fold increase relative to Z-VEGF and >3,300-fold increase relative to α-VEGF-2).…”
Section: S-s S-s S-smentioning
confidence: 99%
“…The unnatural backbone diminishes α/β-peptide susceptibility to proteolytic degradation relative to conventional peptides (α-residues only, "α-peptides"). As a result, α/β-peptides can exhibit improved pharmacokinetic properties in vivo relative to analogous α-peptides (8,9). To date, however, the α/β-peptide strategy has been restricted to mimicry of isolated α-helices, which is a significant limitation given that most protein-protein interactions are mediated by surfaces that are broader than can be covered by a single, regular helix (1-4, 10).…”
mentioning
confidence: 99%
“…In this study, a hexameric β-peptide 14-helix was utilized with a surface engineered to bind to Aβ aggregates. Two-stage binding was observed in the solution phase when the foldameric recognition segments were attached to a tetravalent oligo-lysine dendron template (8). The first stage has a low nanomolar affinity toward Aβ oligomers with fractional stoichiometry indicating that multiple copies of aggregated Aβ chains are necessary to form a surface patch to be recognized by the tetravalent ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin receptor [7] GLP-1 receptor, [8] PTHR1, [9] the p53-hDM2, [10] the BH3-Bcl-x L [11,12] and the VEGF-VEGFR1 [13] interactions, the gp41 virus cell infusion protein assembly [14], the γ-secretase enzyme [15] and amyloid aggregation. [16] Whilst biomimetic molecular recognition can be achieved with foldamers, their application in therapy, diagnostics and as analytical tools is still a major challenge.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation